1990
DOI: 10.1042/bj2710541
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation studies on natural and recombinant bovine prochymosin (prorennin)

Abstract: 1. Prochymosin in solution in the presence of 8 M-urea is fully unfolded, as indicated by its fluorescence spectrum, fluorescence quenching behaviour and far-u.v. c.d. spectrum. 2. Equilibrium studies on the unfolding of prochymosin and pepsinogen by urea were carried out at pH 7.5 and pH 9.0. The results indicate that the stabilization energies of the two proteins are identical at pH 7.5, but that at pH 9.0 pepsinogen is significantly less stable than prochymosin. 3. Kinetic studies on the unfolding of prochy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The inclusion bodies containing His 6 ‐ΔScPTC6p were obtained by centrifugation of the total cell lysate for 10 min at 12 000 g at 4°C. Solubilization of the inclusion bodies was carried out with 8 M urea as previously described (Sugrue et al , 1990). Denatured His 6 ‐ΔScPTC6p proteins in the above solution was refolded and dialyzed as previously described (Rudolph & Lilie, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion bodies containing His 6 ‐ΔScPTC6p were obtained by centrifugation of the total cell lysate for 10 min at 12 000 g at 4°C. Solubilization of the inclusion bodies was carried out with 8 M urea as previously described (Sugrue et al , 1990). Denatured His 6 ‐ΔScPTC6p proteins in the above solution was refolded and dialyzed as previously described (Rudolph & Lilie, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Even though the refolding process of rhizopuspepsin is not fully reversible, denaturation studies with the aspartic proteinase prochymosin have also shown that the recombinant protein is directly comparable to the native enzyme (Sugrue et al, 1990). Because extensive denaturation studies have not been carried out on mutants of the aspartic proteinases, the trends seen in the change in stability of the large library of mutants and their crystal structures may be useful in rationalizing the change in the denaturation parameters seen for the mutants of rhizopuspepsin ( Fig.…”
Section: W T Lowther Et Almentioning
confidence: 99%
“…Although these can be easily isolated, subsequent recovery of the entrapped prochymosin requires extensive solubilisation and in vitro refolding, prior to acid activation to produce mature chymosin [51][52][53][54][55]. In the case of chymosin A the additional possibility of autolysis to give the low activity C2 form may lower the yield Eukaryotic expression systems for chymosin include the yeasts Saccharomyces cerevisiae and Kluyveromyces lactis and the filamentous fungus Aspergillus [60,611. In the S.cerevisiae system a high proportion (approximately 80%) of the invertaseprochymosin fusion product was secreted, but the best overall amount of 20 mg 1-1 of activated material was obtained only after the screening of a large number of transformed colonies for super-secreting mutants [62].…”
mentioning
confidence: 99%